RANCANG BANGUN ANTENNA WAJANBOLIC DENGAN DIAMETER 46 CENTIMETER PADA FREKUENSI 1900 MHz UNTUK MEMPERKUAT PENERIMAAN SINYAL WCDMA - Nafik, Ichsyan; Yuniarto, Yuniarto (Gema Teknologi, 2012)
Ichsyan Nafik, Yuniarto, in paper a 1900 MHz, 46 cm wajanbolic antenna design to strengthen wcdma signal reception explain that the antenna is a device used to transmit or receive electromagnetic waves electromagnetic waves. Reception using an antenna will amplify the signal acquisition in accordance with the ability of the antenna itself. Signal instability that often occurs in WCDMA networks makes the need for strengthening the acquisition of the signal is very large. Antenna Wajanbolic is one option reinforcement signal acquisition. In WCDMA networks, downlink frequency used at 2100 MHz, while the uplink frequency to 1900MHz. Antenna wajanbolic Must ditune to resonate in the uplink frequency is 1900 MHz. The final project focuses on making wajanbolic antenna for Line of Sight (LoS) who works at a frequency of 1900 MHz for WCDMA (3G). In accordance with the name wajanbolic antenna, this antenna uses a reflector from the pan, with a waveguide of modified pipes are coated with aluminum duct tape, and a signal receiver using a USB 3G modem. From the results of the testing and analysis of the results showed that wajanbolic antenna is directional antenna that has the directivity signal. This wajanbolic got an antenna gain of 16 dB value. Keyword: wajanbolic antenna, WCDMA, Line of Sight (LOS)